Archaeological Perspectives on Warfare on the Great Plains - Bamforth, Douglas B.; Clark, Andrew J. (Archaeologist) (Book collections on Project MUSE., 2018)
"Anthropologists from across the Plains critically examine regional themes of warfare from pre-Contact and post-Contact periods and assess how war shaped and reflected human societies on the Plains. Brings together research from across the region, provides unprecedented evidence of the effects of war on tribal societies"--Provided by publisher.